Effects of Dietary Plant-Derived Anti-Coccidia on the Production Performance and Oocyst Output of Broiler Chickens - Naag, Hazel M.; Purnamasari, Listya; Olarve, Joseph P.; dela Cruz, Joseph Flores (Buletin Peternakan, 2025)
Adding feed additives to combat coccidiosis, such as anti-coccidial drugs to broiler diets, can lead to side effects, meat residues, and antimicrobial resistance issues. Alternatively, plant-derived anti-coccidia could serve as safe and simple alternatives compared to synthetic/chemical feed additives. The objective of this study was to evaluate the production performance and oocyst output of broilers fed diets with plant-derived anti coccidia. A total of 300 day-old Cobb 500 broiler chicks were randomly assigned in 30 cages in a completely randomized design with 3 treatment groups, 10 replicates per treatment of 10 chicks per cage. The treatment diets were fed for 35 days: basal diet without anti-coccidia (T1), 500ppm synthetic anti-coccidia containing Narasin and Nicarbazin (T2), and 500ppm plant-derived anti-coccidia containing Cinnamomum camphora, Elephatopus scaber, and Valeriana walichii (T3). Results showed significant differences (p<0.05) in the average body weight gain, feed intake, feed efficiency, and income over feed and chick cost among the three treatment groups. Fecal analysis results showed the absence of oocysts in those feeds with synthetic anti-coccidia and plant derived anti-coccidia. T3 that contains plant-derived anti-coccidia has the highest growth performance among other treatments. In conclusion, plant-derived anti coccidia can be used as an alternative anti-coccidial drug without compromising the growth performance of broiler chickens